Pola Sebaran dan Rendemen Hasil Gliserolisis Enzimatis Campuran CPO (Crude Palm Oil) dan PKO (Palm Kernel Oil) - Fizzaria Khasbullah; Murhadi Murhadi; Nurleni Kurniawati; Bigi Undadraja; Widia Rini Hartari (Politeknik Negeri Lampung., 2022)
The use of oil in the food and non-food industries is increasing with the increasing number of findings on oleochemical synthesis processes that can be applied on an industrial scale. MAGs and DAGs are used as part of fat products and are often associated with other emulsifiers. MAG synthesis can be carried out chemically and enzymatically. The glycerolysis process using lipase enzymes as biocatalysts requires relatively low energy and produces products with better quality. This study uses enzymatic glycerolysis and will observe the distribution pattern of the glycerolysis product which describes the level of completeness of the reaction. The distribution pattern that describes the perfection of the reaction is a distribution pattern that has spots that spread regularly (not random/straight). The experiment was carried out with a single factor and two replications. The data are presented in the form of tables and histograms, then the results are discussed descriptively. Treatment factors, namely the ratio of the mixture of CPO and PKO consisting of 11 ratios of CPO and PKO: 0.2; 0.4; 0.6; 0.8; 1.0; 1,2; 1.4; 1.6; 1.8 and two controls. Based on the observations made, the glycerolysis of a mixture of CPO and PKO in various ratios, produces a pattern of distribution on the TLC plate which is regular and the Rf (Retardation factor) value shows that from closest to furthest are MAG, DAG, ALB, and TAG with Rf 0.01; 0.12; 0.31; 0.57, respectively. The highest MAG yield was produced by the results of glycerolysis of CPO control (83.90%) followed by PKO control (74.90%) and a mixture of CPO-PKO with a ratio of 0.8 (73.71%). The highest yield of MAG-DAG was produced by a mixture of CPO-PKO with a ratio of 1.6 (93.21%) followed by CPO control (91.88%) and a ratio of 0.8 (73.71%). Key Word: CPO, enzymatic glycerolysis, MAG, PKO, TLC.